2006
DOI: 10.1080/10635150601058014
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Morphological Convergence and Rapid Radiation in the Evolutionary History of the Family Geoemydidae (Old World Pond Turtles) Revealed by SINE Insertion Analysis

Abstract: The family Geoemydidae is one of three in the superfamily Testudinoidea and is the most diversified family of extant turtle species. The phylogenetic relationships in this family and among related families have been vigorously investigated from both morphological and molecular viewpoints. The evolutionary history of Geoemydidae, however, remains controversial. Therefore, to elucidate the phylogenetic relationships of Geoemydidae and related species, we applied the SINE insertion method to investigate 49 inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 53 publications
3
33
0
Order By: Relevance
“…Short interspersed elements (SINEs) are one of the major types of mobile elements in vertebrate genomes and are generally lineage-specific [Ohshima and Okada, 2005]. SINEs are among the first retroposons to be very extensively studied in sauropsid genomes [Endoh and Okada, 1986;Endoh et al, 1990;Smit and Riggs, 1995;Ohshima et al, 1996;Okada et al, 1997;Terai et al, 1998;Gilbert and Labuda, 1999;Fantaccione et al, 2004;Sasaki et al, 2004;Bejerano et al, 2006;Kosushkin et al, 2006Kosushkin et al, , 2008Nishihara et al, 2006;Piskurek et al, 2006Piskurek et al, , 2009Sasaki et al, 2006;Piskurek and Okada, 2007;Shedlock et al, 2007;Gogolevsky et al, 2008;Hirakawa et al, 2009]. The first sauropsid SINE to be discovered was polIII/SINE in turtles [Endoh and Okada, 1986;Endoh et al, 1990], and its LINE partner is CR1 LINE [Ohshima et al, 1996;Kajikawa et al, 1997].…”
Section: Non-ltr Retrotransposons or Retroposonsmentioning
confidence: 99%
“…Short interspersed elements (SINEs) are one of the major types of mobile elements in vertebrate genomes and are generally lineage-specific [Ohshima and Okada, 2005]. SINEs are among the first retroposons to be very extensively studied in sauropsid genomes [Endoh and Okada, 1986;Endoh et al, 1990;Smit and Riggs, 1995;Ohshima et al, 1996;Okada et al, 1997;Terai et al, 1998;Gilbert and Labuda, 1999;Fantaccione et al, 2004;Sasaki et al, 2004;Bejerano et al, 2006;Kosushkin et al, 2006Kosushkin et al, , 2008Nishihara et al, 2006;Piskurek et al, 2006Piskurek et al, , 2009Sasaki et al, 2006;Piskurek and Okada, 2007;Shedlock et al, 2007;Gogolevsky et al, 2008;Hirakawa et al, 2009]. The first sauropsid SINE to be discovered was polIII/SINE in turtles [Endoh and Okada, 1986;Endoh et al, 1990], and its LINE partner is CR1 LINE [Ohshima et al, 1996;Kajikawa et al, 1997].…”
Section: Non-ltr Retrotransposons or Retroposonsmentioning
confidence: 99%
“…This presumption appears to be very unlikely because it was deduced from the hypothesis that the genus Ocadia is allied to the "Batagur complex" (McDowell 1964) consisting of Batagur baska sensu lato, B. borneoensis, Chinemys, Heosemys annandalii, Malayemys, and Ocadia. However, recent molecular phylogenetic analyses showed that the "Batagur complex" is not monophyletic (e.g., Barth et al 2004;Spinks et al 2004;Sasaki et al 2006). This suggests that O. tanegashimensis from the Kawachi Formation may have been transported from a nearby lowland area via a river.…”
Section: Discussionmentioning
confidence: 90%
“…Recent molecular phylogenetic analyses have shown that the genus Ocadia is included in a clade with Chinemys spp. and Mauremys japonica and that these taxa form another more inclusive clade with the remaining living species of Mauremys (Mauremys sensu lato, Honda et al 2002;Barth et al 2004;Feldman and Parham 2004;Spinks et al 2004;Sasaki et al 2006;Jiang et al 2011). However, no synapomorphic morphological character states are known for the two clades (e.g., Honda et al 2002;Hirayama et al 2007).…”
Section: Systematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shaffer et al (1997) used a combination of molecular and morphological data to suggest a possible close affinity of Chinemys with Heosemys. Moreover, more recent molecular studies have yielded phylogenetic trees on which Chinemys, as well as the genus Ocadia, are consistently located within a cluster with the genus Mauremys (Wu et al 1998;McCord et al 2000;Honda et al 2002;Barth et al 2004;Spinks et al 2004;Feldman and Parham 2004;Sasaki et al 2006;Jiang et al 2011). In contrast, Parham et al (2001) presented a phylogenetic hypothesis based on molecular data where C. reevesii and C. nigricans were clearly separated from Mauremys species recognized at that date.…”
Section: Conservation Biology Of Freshwater Turtles and Tortoisesmentioning
confidence: 99%